2021
DOI: 10.1007/s10555-021-09998-8
|View full text |Cite
|
Sign up to set email alerts
|

Debris-stimulated tumor growth: a Pandora’s box?

Abstract: Current cancer therapies aim at eradicating cancer cells from the body. However, killing cells generates cell “debris” which can promote tumor progression. Thus, therapy can be a double-edged sword. Specifically, injury and debris generated by cancer therapies, including chemotherapy, radiation, and surgery, may offset their benefit by promoting the secretion of pro-tumorigenic factors (e.g., eicosanoid-driven cytokines) that stimulate regrowth and metastasis of surviving cells. The debris produced by cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 153 publications
(326 reference statements)
2
13
0
Order By: Relevance
“…Notably, among those 67 proteins, we found HMGB1 (high mobility group protein B1) (Fig. 3 S) which, in addition to its role as a nuclear non-histone protein is involved in the regulation of transcription and chromatin remodeling, has a critical role as a DAMP that can be secreted outside a cell and participate in the activation of tumor cell repopulation [ 5 , 27 ]. The latter function of HMGB1 allowed us to propose it as a key player in complex with Hsp70.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, among those 67 proteins, we found HMGB1 (high mobility group protein B1) (Fig. 3 S) which, in addition to its role as a nuclear non-histone protein is involved in the regulation of transcription and chromatin remodeling, has a critical role as a DAMP that can be secreted outside a cell and participate in the activation of tumor cell repopulation [ 5 , 27 ]. The latter function of HMGB1 allowed us to propose it as a key player in complex with Hsp70.…”
Section: Resultsmentioning
confidence: 99%
“…After receiving a signal, most often from the tumor microenvironment (TME), quiescent cells trigger their intrinsic mechanisms to induce proliferation and terminate the relapse cycle [ 4 ]. The remnants of dying tumor cells or so-called DAMPs (Damage-Associated Molecular Patterns) are found among the inducers of repopulation; these proteins, sometimes also called alarmins, were found to be released from dead or living cells [ 5 ]. However, it is not entirely clear how the debris of dying tumor cells or alarmins can induce proliferation and further relapse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More notably, increased expression of pro-apoptotic proteins was also observed in low-dose treatments that induced the promotion of tumor growth. Emerging evidence has indicated that cell apoptosis could facilitate tumor growth and is correlated with poor prognosis and disease-free survival in certain types of cancer such as breast, head and neck, and colon cancer ( 46 , 47 ). Chang et al ( 28 ) demonstrated that 5-FU-generated tumor cell debris stimulated tumor growth by triggering the release of OPN from tumor cells in subcutaneous and orthotopic models of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Within this pro-inflammatory milieu, tumor cells can proliferate while circumventing death and invading new tissues by releasing growth factors, survival factors, and proangiogenic factors [39,[83][84][85][86][87]. Several pro-inflammatory mediators, such as TNF-α, IL-6, transforming growth factor beta (TGF-β), IL-10, CCL2, and CCL20, have been shown to attract macrophages and participate in both the initiation and progression of cancer [82,88,89].…”
Section: Inflammation In Cancermentioning
confidence: 99%